Temporal Heterogeneity Metrics in Apoptosis Induced by Anticancer Drugs. (July 2015) - Vorobjev, Ivan; Barteneva, Natasha S.
The apoptotic process is highly heterogeneous and asynchronous. A long-standing question is how many parameters define the time and reversibility of the apoptotic response at a single-cell level. We characterized at the single-cell and population levels the time sequence of apoptotic events in response to anti-cancer drugs using extrinsic and intrinsic apoptotic stimuli. We show that the temporal sequence of major apoptotic events is the same in response to all anti-cancer drugs studied: the apoptotic volume decrease and Na + influx occur rapidly and are tightly coordinated with mitochondrial outer membrane depolarization (MOMP), mitochondrial inner membrane depolarization and a decrease in the production of reactive oxygen species (ROS). Phosphatidylserine externalization usually starts after MOMP and precedes caspase 3/7 activation. Activation of caspases 3/7 is a slow process that always starts after MOMP, with significant delay. Cell-to-cell variability of the MOMP onset is described by Gaussian distribution, whereas the γ-distribution model describes cellular variability in the duration of MOMP-to-caspase activation stages. Cells from the pre-MOMP stage to the after-caspase 3/7 activation stage coexist for many hours. We demonstrated by FACS that cells in the pre-MOMP stage can recover after apoptotic stimuli, rarely recover after MOMP but before caspase 3/7 activation, and are unable to recover after caspase 3/7 activation. We propose a double-stroke model for apoptosis execution.